2017
DOI: 10.1186/s12888-017-1528-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical activity and motivation, competence, functioning, and apathy in inhabitants with mental illness from a rural municipality: a cross-sectional study

Abstract: BackgroundThere is increasing evidence for physical activity (PA) having a positive impact on physical and mental health as well as illness symptoms in individuals with severe mental illness (SMI). However, individuals with SMI experience several barriers that makes it difficult to take advantage of the benefits associated with PA. One barrier consistently reported to impede PA is motivational issues. Thus, the main aim of the present study was to examine associations between PA and motivation for PA, perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 66 publications
0
15
0
3
Order By: Relevance
“…Our study ndings showed a high burden of CMDs in university students, which was associated with an increased likelihood of perceived barriers to exercise. Poor mental health functioning is associated with a lack of energy and motivation for PA engagement, creating a vicious cycle of poor physical and mental health [35,36]. Also, participants with chronic conditions reported more exercise barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Our study ndings showed a high burden of CMDs in university students, which was associated with an increased likelihood of perceived barriers to exercise. Poor mental health functioning is associated with a lack of energy and motivation for PA engagement, creating a vicious cycle of poor physical and mental health [35,36]. Also, participants with chronic conditions reported more exercise barriers.…”
Section: Discussionmentioning
confidence: 99%
“…All in all, this situation is probably not unique to this particular institution. Individuals with psychiatric illness often want to become more physically active (36). However, perceived barriers and the quality of their motivation make them need help, support and high-quality activity possibilities (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In order to help patients with severe mental illnesses to engage in PA, the sessions should match the patients' abilities and (psychosocial) needs [38]. Measures that may help are structured training in a facility [37], social support [37,[39][40][41][42], the support of an exercise instructor [37,39], the promotion of intrinsic and extrinsic motivation (empowering patients to control their training independently) [36,43,44], motivational interviewing, and goal setting [45]. In addition to pursuing physiological goals, it is also recommended to make use of exercise programs that provide psychological support to patients [40] and promote interaction with others [46].…”
Section: Physical and Psychological Activationmentioning
confidence: 99%